Biological Approaches for Controlling Weeds - Radhakrishnan, Ramalingam (IntechOpen, 2018)
Weed populations in agriculture are a major cause of yield loss. Conventionally, crop rotation and tillage practices limit the number of weed flora. Several chemical herbicides are being applied to control weed growth, but the long-term use of those chemicals does not effectively control weeds, due to the development of resistant germplasms, which cause hazardous effects in living organisms. The global interest in organic farming endorses the alternative way of weed control against chemical herbicides. Recently, biological agents have been added to integrated weed management strategies. Several studies reveal that plant extracts, bacteria, fungi and their products effectively control weed seed germination and growth. The aim of this book is to discuss the current understanding of bioherbicides and strategies to weed control.